Distribution of dihydrofolate reductase (dhfr) and dihydropteroate synthase (dhps) mutant alleles in Plasmodium vivax isolates from Thailand - Pimwan Thongdee (2018)
The analysis of prevalence and distribution of pvdhfr and pvdhps mutations were performed in 169 samples collected from patients with Plasmodium vivax infection who attended the malaria clinics in the provinces along the three international borders of Thailand (Thai-Myanmar, Thai-Cambodian, and Thai-Malaysian borders). SNP-haplotypes of the pvdhfr at amino acid positions 13, 33, 57, 58, 61, 117, and 173 and of the pvdhps at positions 383 and 553 were examined by nested PCR-RFLP. Significant differences in the prevalence and distribution of pvdhfr and pvdhps combination alleles were observed in P. vivax isolates collected from all the three border areas. The most pr evalent combination alleles were triple mutant pvdhfr 57L/58R/117T alleles/double wild-type pvdhps alleles (n=18), double mutant pvdhfr 58R/117N alleles/double wild-type pvdhps alleles (n=10), and triple mutant pvdhfr 58R/61M/117N alleles/double wild-type pvdhps alleles (n=52) or with single mutant pvdhps 383G allele (n=28), respectively. These information on prevalence and patterns of pvdhfr and pvdhps polymorphisms obtained from the present study suggest the presence of SP pressure on P. vivax isolates in Thailand which could be linked to the introduction of malaria from neighboring countries. Results did not support the application of SP for P. vivax control program in Thailand as well as the neighboring countries. © 2013 Elsevier B.V.